All Polarization Maintaining Brillouin Erbium-Doped Fiber Laser With Sub-kHz Linewidth Using Saturated Absorber and Self-Injection Feedback - Junsen Yang; Zhengkang Wang; Jianming Shang; Shiyou Xiao; Zhixue Li; Bin Luo; Tianwei Jiang; Song Yu (IEEE Photonics Journal)
A narrow-linewidth all-polarization-maintaining (PM) Brillouin erbium-doped fiber laser (BEFL) is proposed and demonstrated experimentally, which employs erbium-doped fiber (EDF) acting as both the linear gain and the Brillouin gain medium. In order to realize a single longitudinal mode (SLM) operation and a narrow linewidth fiber laser output, the saturable absorber (SA) and the optical self-injection feedback structure are employed in the BEFL for the first time. In this experiment, three sets of comparative experiments are conducted to demonstrate the effectiveness of the SA and the self-injection feedback structure. The experimental result shows that the SA structure can eliminate transient multimode phenomena and narrow the linewidth, and the self-injection feedback structure can act as an effective mode filter and a compound-cavity to make the intracavity mode purer. A stable SLM operation of the BEFL is verified by the delayed self-heterodyne system, which thanks to the adding of the SA and the self-injection feedback structure. The BEFL's wavelength stability detected by is less than 0.0045 nm over 14 hours. In addition, an ultra-narrow linewidth of approximately 224 Hz is obtained.